OPTIMIZATION OF INTERSECTION PERFORMANCE AND VEHICLE TRAFFIC FLOW AT INTERSECTION FOUR DHOHO PLAZA KEDIRI CITY USING MKJI METHOD 1997 - Hidiyati, Evita Fitrianis; Nugroho, Laksono Djoko; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
Kediri is the third largest city in East Java after Surabaya and Malang with a population growth of 289,418 people in 2023. The International Airport will open at the end of 2023 in Kediri. However, rapid population growth has also led to an increase in mobility and the number of motorized vehicles on the streets of Kediri City, including at the research site in Dhoho Plaza. The analysis of the signaled intersection was carried out using the MKJI 1997 method, and Visual PTV Vissim for three days on Monday, Friday, and Sunday. Based on the results of the analysis, a cycle time of 90.7 was obtained which affected saturation in each arm of the intersection. There is a potential reduction in signal light waiting time from 135 seconds to 118 seconds by repairing side obstacles. The solution to overcome side obstacles is to improve facilities such as traffic lights and adjust the timing of signal lights. The change in the value of side barriers also has a significant impact on waiting times, queues, and fuel costs at the intersection of Pasar Pahing, with congestion cost efficiency reaching Rp. 22,679,183 in the next 5 years.